Significant increase in eco-efficiency of China’s grain production from 2000 to 2022: Trend changes, typological evolution, and driving factors - Huali Jin; Chao Han (PLoS ONE, 2025)
Enhancing the eco-efficiency of grain production is a critical avenue for ensuring food security and ecological sustainability. This study employs a global super-efficiency SBM model incorporating undesirable outputs, combined with the life cycle assessment method, to comprehensively measure the eco-efficiency of grain production in 31 Chinese provinces and municipalities from 2000 to 2022. Furthermore, we conduct a comprehensive analysis of the distributional dynamics and key driving factors of the eco-efficiency of grain production. The findings indicate that: (1) The overall level of eco-efficiency in China’s grain production is relatively low, exhibiting significant regional disparities. The spatial pattern follows the gradient of “major grain-producing regions> production-sales balance regions> the major grain-consuming regions,” with most provinces yet to reach the efficiency frontier. (2) The eco-efficiency of grain production in China generally exhibits an upward trend, although there are indications of spatial polarization, evident “club convergence” characteristics, and a notable “positive spillover” effect. (3) The eco-efficiency of grain production in China is influenced by a complex interplay of factors, including economic, social, technological, demographic, and natural elements. The gross total agricultural output, water resources endowment, and structure of agricultural production emerge as the critical driving factors, manifesting the Matthew effect of “the rich getting richer and the poor getting poorer.” The findings of this study provide a foundation for the refinement of sustainable grain production policies and the promotion of green agricultural transformation.